Two Input Buck-Boost Integrated Soft-Switched Ripple Free LED Driver with Reduced Voltage Stress - Narender Jatoth (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this research paper, a two input buck-boost integrated light emitting diode (LED) driver using full bridge is proposed. Two different input dc voltages are connected in anti-series across full bridge. Due to this, voltage stress across each semi-conductor switch is low. An LC resonant circuit in full bridge converter is used to achieve soft-switching. Thus, proposed ripple free LED driver energy efficiency is improved due to low switching transition power. Further, the current in LC series circuit is completely decided by difference in two input voltages. LED lamp is powered by using interleaved inductor configuration, which reduces the ripple in lamp current. This feature helps its suitability in future dc-grid lighting applications. Modified buck-boost configuration is used at the input side for constant lamp current regulation. Proposed converter steady-state operation is performed using numerical simulations. A 36 W experimental prototype is also made to verify the simulation results.